Staging identity: When poets read themselves and their translations - Larisa Cercel (JoSTrans: The Journal of Specialised Translation)
The article deals with a new subject of translatological research: the translator’s own reading, namely the public reading or performance of a translation by the translator themselves. This genre (Cercel 2020) is intimately related to the question of identity, given that the translator presents his or her own translation to the audience. That translation bears the inevitable mark of his or her individuality and moreover involves the affirmation of his or her identity as the author of the translated text. The translation-performance nexus in the translator’s act of reading will be explored in the essay in terms of the parameters of (a), the voice, (b), the public persona and (c), the effect of the performance. Dealing with the phenomenon of ‘voice’ offers direct access to the identity of a translator because “the uniqueness of the person is represented by the voice. The voice is the expression of the person, and more importantly, it is the essence of the person” (Pajević, 2002, p. 240). The term “public persona” goes back to Carl Gustav Jung (1974) and refers to the outwardly displayed attitude of a person that serves as a vehicle for his or her adaptation — or conversely non-adaptation — to social conventions and expectations, and which is closely related to his or her self-image and identity. The “effect” (Fischer-Lichte, 2003) provides information about the audience’s perception of and reaction to the given performance and the translator’s identity statement contained therein. These parameters will be examined on the basis of a historical corpus, namely that of Paul Celan’s readings of his poems and translations.